Kant in the XIXth-century disputes on metaphysics - Noras, Andrzej J. (Folia Philosophica, 2009)
The paper tries to systematize the views on metaphysics in the XIXth-century in broadly taken pre-neokantian and Neo-Kantian movement. Taking the Kantian notion of the “thing-in-itself” as a central one I point it as a key to the XIXth-century metaphysics. Hence Jacobi, who was first to point the importance of this problem, needs to be considered as a central figure. The analysis of Neo-Kantianism - and especially its metaphysical current - shows that even its representatives were unable to notice the problem of the thing-in-itself. It can be witnessed in the most famous book of this current, that is in Kant und die Epigonen by O. Liebmann. The outcome of the presented discussion is that Neo-Kantianism did not contribute to a metaphysical interpretation of Kant in the XIXth-century, and the dispute on the understanding of being begins only in 1920s with a publication of the works by Nicolai Hartmann and Martin Heidegger.